CFD INVESTIGATION OF COMPLEX PHENOMENA IN S-SHAPE REGION OF REVERSIBLE PUMP-TURBINE - Jacquet, Clement; Patella, Regiane Fortes; Balarac, Laetitia; Houdeline, Jean Bernard; Silva, Everton Torquato da (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Pumped Storage Plants (PSP) using reversible pump-turbines offer the possibility to store large amounts of energy with high efficiency and at reasonable cost. For reversible high head pump-turbines, the characteristic curves exhibit an S-shape in the turbine, turbine break and reverse pump quadrants. This S-shape leads to unstable behaviour of the turbine when coupling to the grid (for small guide vane opening) or to surge transient phenomena in case of emergency shutdown (for large guide vane opening). Typically the piping system can be exposed to severe pressure oscillations. Furthermore, the flow inside the pump-turbine is characterized by unsteady complex hydrodynamic phenomena. These phenomena have to be deeply investigated to improve the behaviour of the pump-turbine in such operating conditions. This paper focuses on the numerical analysis of the flow in a reversible pump-turbine in the S-shape region. For this application, we used unsteady computation applying the SAS-SST turbulence model and considered a full computational domain that includes all the components of the pump-turbine. The study highlights the evolution of the flow behaviour for a large range of operating conditions: from the optimal efficiency point to the zero discharge condition, for a given constant guide vane opening.